The effectiveness of the supports available for promoting inclusion in three early childhood education and care settings in Ireland - Moran, Sinead; Twomey, Miriam; Lynam, Aoife; Mc Guckin, Conor (My University, 2023)
This article, based on an M. Ed undertaken in 2019 reiterates how, in recent years, while significant attention has been directed towards ensuring the inclusion of all children in Early Childhood Education and Care (ECEC) settings in Ireland, some areas may still need addressing. To help identify some of these areas, the authors undertook a small-scale research study, which explored the lived experiences of a group of those supporting three children’s access to the ECCE scheme. Each of the research participants were direct partners within the microsystem of the children who were accessing the ECCE scheme, and required additional supports for full participation in the scheme. Thus, this article adds to our knowledge and understanding of how SDG 4 and 10 can be achieved in the Irish context. Overall, the study aligns with the objectives of United Nations Sustainable Development Goal (SDG) 4 which aspires to ensure equitable access to ECEC for all children by 2030 (UNESCO, 2023). In this context, this small-scale study offers further insights into Ireland’s progress toward achieving this goal. (For more information on Ireland’s attainment of SDG4, as it relates to ECEC, see article 3, this volume, by Mary Moloney).
PUBLISHED